Intravenous caffeine versus intravenous ketorolac for the management of moderate to severe migraine headache (Bangladesh Journal of Pharmacology, 2016)
The aim of this study was to determine if intravenous caffeine is as effective as intravenous ketorolac for the treatment of moderate to severe migraine headaches. Eligible patients randomly received 60 mg caffeine citrate or 60 mg ketorolac infused intravenously. Their pain score were measured at baseline, one hour and two hours after infusion. Therapeutic success was defined as decreasing of at least 3 points on the pain score. In total 110 patients were enrolled (75.5% women). Therapeutic success after 60 min was achieved by 63.6% of patients in the caffeine and 70.1% of patients in the ketorolac group (p = 0.23). After 120 min, 87.3% of the caffeine group and 83.6% of the ketorolac group achieved therapeutic success (p = 0.49). In this multi-center, randomized double blind study, intravenous caffeine was as effective as intravenous ketorolac for first line abortive management of acute migraine.